Ferulic acid derived binary acyl chloride compound, copolymerization modified para-aramid resin as well as preparation method and application of ferulic acid derived binary acyl chloride compound and copolymerization modified para-aramid resin

By introducing ferulic acid-derived binary acid chloride to break the regularity of para-aramid molecular chains, combined with copolymerization modification method, the problems of molecular weight loss and mechanical strength reduction of traditional para-aramid in the dissolution of concentrated sulfuric acid are solved, and its dissolution is improved It is suitable for lithium-ion battery separator materials for new energy vehicles.

CN119285463APending Publication Date: 2025-01-10NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI

Patent Information

Application Number
CN202411408004.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-09
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Traditional para-aramid material loss during the dissolution of concentrated sulfuric acid, corrosion protection of processing equipment and employee safety issues, and existing improved methods damage the mechanical strength of the material when improving solubility, making it difficult to meet the lithium-ion battery separator materials of new energy vehicles High requirements for flexibility.

Method used

Introducing ferulic acid-derived binary acid chloride as an asymmetric third monomer, breaks the regularity of para-aramid molecular chains, enhances solubility, and improves flexibility through copolymerization modification method while retaining high mechanical strength, using biomass Derivatize the binary acid chloride structure to simplify the preparation process.

Benefits of technology

It exhibits good solubility in various solvents, improves the processability and flexibility of para-aramid, maintains high mechanical strength, simplifies the preparation process, and solves the disadvantages of traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285463A_ABST
    Figure CN119285463A_ABST
Patent Text Reader

Abstract

The invention discloses a ferulic acid-derived binary acyl chloride compound, a copolymerization modified para-aramid resin, and a preparation method and application of the ferulic acid-derived binary acyl chloride compound and the copolymerization modified para-aramid resin. The structural formula of the copolymerization modified para-aramid resin is as follows: # imgabs0 #, wherein m: n = (90-99): (10-1). According to the invention, an asymmetric third monomer ferulic acid derived binary acyl chloride is introduced into a traditional para-aramid fiber structure for modification, so that the dissolvability of the material is enhanced, and the flexibility of the material is improved while the relatively high mechanical strength of the original para-aramid fiber is maintained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of organic synthesis and polymer material synthesis, and specifically relates to a ferulic acid-derived dibasic acid chloride compound and a preparation method thereof, as well as a copolymer-modified para-aramid resin and a preparation method thereof. Background Art

[0002] Poly(p-phenylene terephthalamide) fiber (para-aramid fiber) is known as one of the three high-performance fibers together with carbon fiber and ultra-high molecular weight polyethylene fiber. Para-aramid is widely used in high-end application scenarios such as rail transit, aerospace, and national defense due to its excellent thermodynamic properties. Traditional para-aramid exhibits excellent solvent resistance due to its high crystallinity and high orientation. The only commonly used processing solvent is concentrated sulfuric acid. The process of concentrated sulfuric acid dissolving para-aramid materials will be accompanied by the digestion of part of the resin, resulting in a decrease in molecular weight loss. In addition, para-aramid dissolves slowly in concentrated sulfuric acid. The use of concentrated sulfuric acid as a solvent also puts forward higher standards for the corrosion resistance of subsequent processing equipment and employee safety protection. Invention patent CN118007259A discloses a method for improving the solubility of para-aramid by in-situ copolymerization. This method improves the solubility and processing ability of para-aramid by introducing some meta-structure monomers to break the molecular chain regularity of para-aramid. However, this method significantly weakens the mechanical strength of the material while improving the solubility and processing ability of para-aramid.

[0003] On the other hand, with the rapid development of new energy vehicles, lithium-ion batteries, as their core technology, have become a hot topic for breaking through battery technology. Diaphragm materials are one of the key technologies that restrict the development of lithium-ion batteries for new energy vehicle batteries. Poly(p-phenylene terephthalamide) (PPTA) materials have shown good supporting mechanical properties in new lithium-ion battery composite diaphragms, and at the same time have good ion transport and thermal stability, and are expected to become a new type of lithium-ion battery composite diaphragm material. As a base material for battery diaphragms, para-aramid is required to maintain its original properties while also placing higher requirements on its flexibility. Invention patent CN1 15663394A addresses the problem of para-aramid being difficult to process, and discloses a new solvent system for processing para-aramid. The prepared aramid ceramic composite diaphragm has a high needle puncture strength and can be used as a lithium-ion battery diaphragm material. However, this method requires the use of a variety of dissolution aids when dissolving the para-aramid material, and the processing process is complicated.

[0004] Therefore, how to improve the processability of para-aramid and appropriately increase its toughness while maintaining the high strength characteristics of aramid to meet the higher requirements of the application field of aramid materials is an urgent problem to be solved. Summary of the invention

[0005] The main purpose of the present invention is to provide a copolymer modified para-aramid resin and a preparation method and application thereof, so as to overcome the deficiencies in the prior art.

[0006] In order to achieve the above-mentioned invention object, the technical solution adopted by the present invention includes:

[0007] One aspect of the present invention provides a ferulic acid-derived dibasic acid chloride compound, the structural formula of the ferulic acid-derived dibasic acid chloride compound is shown in formula (I):

[0008]

[0009] Another aspect of the present invention also provides a method for preparing a ferulic acid-derived dibasic acid chloride compound, which comprises: reacting a ferulic acid-derived dibasic acid with thionyl chloride to obtain a ferulic acid-derived dibasic acid chloride compound;

[0010] Wherein, the ferulic acid-derived dibasic acid has a structure shown in formula (II):

[0011]

[0012] Another aspect of the present invention also provides the use of the above-mentioned ferulic acid-derived dibasic acid chloride compound in the preparation of copolymer-modified para-aramid resin.

[0013] Another aspect of the present invention further provides a copolymer modified para-aramid resin, the structural formula of the copolymer modified para-aramid resin is shown in formula (III):

[0014]

[0015] Among them, m:n=90~99:10~1.

[0016] Another aspect of the present invention also provides a method for preparing the aforementioned copolymer modified para-aramid resin, which comprises: mixing the aforementioned ferulic acid derived dibasic acid chloride, terephthaloyl chloride and p-phenylenediamine for polymerization reaction to obtain the copolymer modified para-aramid resin.

[0017] Another aspect of the present invention provides a copolymer-modified para-aramid fiber, which is obtained by processing the above copolymer-modified para-aramid resin.

[0018] Another aspect of the present invention provides a solution processing method, which comprises dissolving the copolymer-modified para-aramid resin in a solvent.

[0019] Compared with the prior art, the technical solution of the present invention has at least the following advantages:

[0020] The copolymer modified para-aramid resin provided by the present invention introduces an asymmetric third monomer into the traditional para-aramid structure, breaks the regular arrangement of the original molecular chain, reduces the generation of the crystalline phase, enhances the solubility of the material, and shows good solubility in a variety of solvents, improving the disadvantage that the traditional aramid can only be dissolved and processed with concentrated sulfuric acid; on the other hand, compared with the traditional para-aramid, the third monomer dibasic acid chloride structure provided by the present invention contains a conjugated rigid carbon-carbon double bond and a flexible ether bond structure, so that the copolymer modified aramid material retains the original high mechanical strength of the para-aramid while its flexibility is greatly improved. The third monomer aromatic dibasic acid chloride provided by the present invention is prepared from dicarboxylic acid derived from biomass, and the preparation process is simple, and it can be used for the synthesis of polyamide without subsequent purification. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments recorded in the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0022] Figure 1 This is the hydrogen nuclear magnetic resonance spectrum of the ferulic acid-derived diacyl chloride prepared in Example 1 of the present invention. DETAILED DESCRIPTION

[0023] The present invention will be more fully understood by reading the following specific embodiments. However, it should be understood that the specific embodiments disclosed below are only exemplary of the present invention, and the present invention can be embodied in various forms. Therefore, the specific functional details disclosed herein should not be interpreted as limiting, but only as the basis for the claims and as a representative basis for teaching those skilled in the art to adopt the present invention in different ways in any appropriate detailed embodiment.

[0024] As one aspect of the technical solution of the present invention, it relates to a ferulic acid-derived dibasic acid chloride compound, the structural formula of the ferulic acid-derived dibasic acid chloride compound is shown in formula (I):

[0025]

[0026] As another aspect of the technical solution of the present invention, a method for preparing a ferulic acid-derived dibasic acid chloride compound is provided, comprising: reacting a ferulic acid-derived dibasic acid with thionyl chloride to obtain a ferulic acid-derived dibasic acid chloride compound;

[0027] Wherein, the ferulic acid-derived dibasic acid has a structure shown in formula (II):

[0028]

[0029] In some embodiments, the preparation method comprises: heating a mixed reaction system comprising a ferulic acid-derived dibasic acid, thionyl chloride, a solvent and a catalyst for reflux reaction to obtain a ferulic acid-derived dibasic acid chloride compound.

[0030] In some preferred embodiments, the solvent includes, but is not limited to, any one or a combination of two or more organic solvents such as dichloromethane, dichloroethane, and chloroform.

[0031] In some preferred embodiments, the mass ratio of the solvent to the ferulic acid-derived dibasic acid is 5 to 10:1.

[0032] In some preferred embodiments, the molar ratio of thionyl chloride to the ferulic acid-derived dibasic acid is 1.5-3:1.

[0033] In some preferred embodiments, the catalyst includes but is not limited to N,N-dimethylformamide (DMF). Only a trace amount of catalyst needs to be added to the mixed reaction system, and the present invention does not fix the ratio.

[0034] In some preferred embodiments, the heating reflux reaction is carried out at a temperature of 50 to 80° C. and for a time of 1 to 3 hours.

[0035] In some more specific embodiments, the method for preparing the ferulic acid-derived dibasic acid chloride comprises the following steps:

[0036] 1) adding a certain amount of organic solvent and ferulic acid-derived dibasic acid into a round-bottom flask;

[0037] 2) Add a certain amount of thionyl chloride and a certain amount of catalyst into the flask, and reflux the reaction at a certain temperature for several hours;

[0038] 3) After the reaction is completed, the reaction solution is distilled under reduced pressure to obtain a light grey dibasic acid chloride powder as a reaction product. After the reaction is completed, the organic solvent and unreacted thionyl chloride are removed by distillation under reduced pressure at a certain temperature.

[0039] In a specific synthesis scheme, the main raw material ratio of the reaction is as follows: the molar ratio of the ferulic acid-derived dibasic acid to thionyl chloride is 1:1.5-3, the organic solvent includes any one of dichloromethane, dichloroethane, and chloroform, the catalyst is DMF, and the reaction time is 1-3 hours. The specific synthesis method is any combination within the above range, but is not limited thereto.

[0040] As another aspect of the technical solution of the present invention, it also involves the use of the aforementioned ferulic acid-derived dibasic acid chloride compound in the preparation of copolymer-modified para-aramid resin.

[0041] As another aspect of the technical solution of the present invention, it also relates to a copolymer modified para-aramid resin, the structural formula of the copolymer modified para-aramid resin is shown in formula (III):

[0042]

[0043] The molar ratio of the symmetrical structural unit to the asymmetrical structural unit is m:n=90-99:10-1.

[0044] As another aspect of the technical solution of the present invention, it also relates to a method for preparing the aforementioned copolymer-modified para-aramid resin, which comprises: mixing the aforementioned ferulic acid-derived dibasic acid chloride compound, terephthaloyl chloride and p-phenylenediamine for polymerization reaction to obtain the copolymer-modified para-aramid resin.

[0045] In some embodiments, the preparation method comprises:

[0046] Under protective atmosphere conditions, p-phenylenediamine, a dissolving salt and a polymerization solvent are mixed to obtain a mixed solution;

[0047] The mixed solution, the dibasic acid chloride compound derived from ferulic acid and terephthaloyl chloride are mixed to carry out the polymerization reaction to obtain the copolymer-modified para-aramid resin.

[0048] In some preferred embodiments, the protective atmosphere includes, but is not limited to, a nitrogen atmosphere.

[0049] In some preferred embodiments, the solubilizing salt includes but is not limited to lithium chloride or calcium chloride.

[0050] In some preferred embodiments, the amount of the solubilizing salt added is 2-10% of the mass of the polymerization solvent.

[0051] In some preferred embodiments, the polymerization solvent comprises a polymerization solvent that is substantially free of water.

[0052] In some preferred embodiments, the polymerization solvent includes, but is not limited to, N-methylpyrrolidone (NMP) or N,N-dimethylacetamide (DMAc).

[0053] In some preferred embodiments, the mass ratio of the polymerization solvent to p-phenylenediamine is 5 to 10:1.

[0054] In some preferred embodiments, the preparation method comprises: mixing the ferulic acid-derived dibasic acid chloride compound with terephthaloyl chloride to obtain a mixed monomer, and mixing the mixed solution with the mixed monomer to carry out the polymerization reaction. The polymerization temperature in the present invention should not exceed 20° C. In order to control the temperature not to be too high during the reaction, the acid chloride is added to the amine in batches.

[0055] Furthermore, the content of the ferulic acid-derived dibasic acid chloride compound in the mixed monomer is 1 to 10 mol%.

[0056] Furthermore, the molar ratio of the mixed monomer to p-phenylenediamine is 1.05-1.2:1.

[0057] Furthermore, the preparation method comprises: adding the mixed monomer to the mixed solution in multiple times. The reaction activity of acyl chloride and diamine is high, and the reaction is too violent if added at one time, which is easy to explode.

[0058] In some embodiments, the preparation method includes: heating the obtained reaction system after completing the polymerization reaction, adding an inorganic base for neutralization reaction to obtain a copolymerized aramid resin polymerization stock solution, and then performing post-treatment to obtain a copolymer-modified para-aramid resin.

[0059] In some preferred embodiments, the inorganic base includes but is not limited to any one of calcium hydroxide, sodium hydroxide, potassium hydroxide, or a combination of two or more thereof.

[0060] In some preferred embodiments, the molar ratio of the inorganic base to p-phenylenediamine is 1: 1. A certain amount of the inorganic base is added to neutralize the hydrogen chloride generated during the polymerization reaction.

[0061] In some preferred embodiments, the heating temperature is 80-100°C.

[0062] In some preferred embodiments, the neutralization reaction time is 0.5 to 1 h.

[0063] In some preferred embodiments, the post-treatment includes at least one of heating, freeze drying, and solvent exchange, but is not limited thereto. The post-treatment is performed to remove the solvent in the copolymerized aramid resin polymerization solution.

[0064] In some more specific embodiments, the method for preparing the copolymer-modified para-aramid resin comprises the following steps:

[0065] S1: Under nitrogen atmosphere protection, p-phenylenediamine and solubilizing salt are dissolved in a polymerization solvent that has been fully dehydrated by molecular sieves, and placed in an ice water bath after being fully dissolved;

[0066] S2: adding diacyl chloride monomers (mixed monomers of ferulic acid-derived diacyl chloride compounds and terephthaloyl chloride) in batches, stirring at high speed to carry out polymerization reaction, monitoring the change of the polymerization stock solution temperature during the reaction, controlling the amount of diacyl chloride monomers added so that the temperature of the reaction system does not exceed 20° C., raising the temperature to 80-100° C. after all the diacyl chloride monomers are added, continuing the reaction for a period of time, adding a certain amount of inorganic base to neutralize the hydrogen chloride generated during the reaction, and obtaining a copolymerized aramid resin polymerization stock solution;

[0067] S3: removing the solvent from the obtained resin polymerization stock solution to obtain copolymer-modified para-aramid resin.

[0068] In the specific synthesis scheme, the main raw material ratio of the reaction is as follows: the reaction adopts the method of low-temperature solution polymerization, with NMP or DMAc as the reaction solvent system; lithium chloride or calcium chloride solubilizing salt with a solvent mass fraction of 2 to 10% is added to the reaction system; during the reaction, the dibasic acid chloride is added to the organic solution of the diamine in batches, and the reaction temperature is controlled not to exceed 20°C. The total molar ratio of the dibasic acid chloride to the diamine in the system is 1.05 to 1.2:1, wherein the ferulic acid-derived dibasic acid chloride accounts for 1 to 10 mol% of the total dibasic acid chloride molar fraction; after the reaction is completed, the temperature is appropriately raised, and a certain amount of inorganic base is added to neutralize the hydrogen chloride generated by the reaction to obtain a polymerization stock solution, and finally the solvent in the polymerization stock solution is removed to obtain a copolymer-modified para-aramid resin. The specific synthesis method is any combination of the above ranges, but is not limited thereto.

[0069] As another aspect of the technical solution of the present invention, it also relates to a copolymer modified para-aramid fiber, which is obtained by processing the above copolymer modified para-aramid resin.

[0070] As another aspect of the technical solution of the present invention, it also relates to a solution processing method, comprising dissolving the above-mentioned copolymer-modified para-aramid resin in a solvent.

[0071] In some embodiments, the solvent includes any one or a combination of two or more of N-methylpyrrolidone (NMP), N,N-dimethylacetamide (DMAc), and concentrated sulfuric acid, but is not limited thereto.

[0072] In summary, the present invention proposes a method for improving the structure of the current para-aramid fiber, which can only be processed by dissolving with concentrated sulfuric acid and has poor processability, provides a ferulic acid-derived dibasic acid chloride compound, and provides a method for preparing a copolymerized modified para-aramid fiber material by introducing the dibasic acid chloride into the para-aramid fiber structure. Specifically, the aromatic dibasic acid chloride monomer provided by the present invention has an asymmetric structure, and its introduction into the para-aramid fiber structure can significantly improve its solubility and enhance its processability, and the presence of conjugated double bonds and ether bonds in the structure enables the para-aramid fiber material to retain a relatively high mechanical strength while giving the material a higher toughness.

[0073] The present invention is further described below by way of examples, but the present invention is not limited to the scope of the examples. The reagents and raw materials used in the following examples are commercially available, and the experimental methods without specific conditions are usually carried out under conventional conditions or under conditions recommended by the manufacturers.

[0074] The ferulic acid-derived dibasic acid used in the following examples of the present invention is 3-[4-(carboxymethoxy)-3-methoxyphenyl]acrylic acid, and its structural formula is:

[0075]

[0076] Example 1

[0077] A method for preparing an aromatic dibasic acid chloride:

[0078] 20.71g of ferulic acid-derived dibasic acid was added to a 250mL round-bottom flask containing 115g of dichloroethane, and 25.61g of thionyl chloride and 100μL of catalyst DMF were added. The reaction was refluxed at 50°C for 3h. After the reaction was completed, the liquid raw material and the solvent were removed by vacuum distillation in a 50°C water bath to obtain 18.92g of ferulic acid-derived dibasic acid chloride with a yield of 79.7%. The product obtained by the reaction did not require subsequent treatment and could be directly used in the next copolymerization modification experiment. The hydrogen nuclear magnetic resonance spectrum of the ferulic acid-derived dibasic acid chloride prepared in this example can be found in Figure 1 .

[0079] Preparation of modified para-aramid material based on this aromatic dibasic acid chloride:

[0080] 108g of p-phenylenediamine and 40g of anhydrous lithium chloride are dissolved in 800g of N-methylpyrrolidone solution after dehydration by molecular sieve, and the dissolved system is placed in an ice water bath at 0-4°C, 200.97g of terephthaloyl chloride and 2.89g of ferulic acid-derived diacyl chloride are weighed and mixed, and the sample is added to the polymerization solution four times, and the addition speed is controlled each time so that the temperature does not exceed 20°C. After the polymerization reaction is completed, the temperature is raised to 100°C, and 48.5g of calcium hydroxide is added to neutralize the hydrogen chloride generated by the reaction. After the reaction is completed, the polymerization stock solution is poured into methanol by solute phase separation method to precipitate pure resin, and the resin is dried to obtain the modified para-aramid resin.

[0081] Example 2

[0082] The present embodiment is different from the embodiment 1 in that, in the preparation process of the aromatic dibasic acid chloride, the amount of thionyl chloride added is 28.4 g, and in the preparation process of the modified para-aramid material, the amount of ferulic acid-derived dibasic acid chloride added is 5.78 g.

[0083] Example 3

[0084] A method for preparing an aromatic dibasic acid chloride:

[0085] 20.71g of ferulic acid-derived dibasic acid was added to a 250mL round-bottom flask containing 115g of dichloroethane, and 28.4g of thionyl chloride and 100μL of catalyst DMF were added, and the reaction was refluxed at 75°C for 2h. After the reaction, the liquid raw material and the solvent were removed by vacuum distillation in a 50°C water bath to obtain 18.9g of ferulic acid-derived dibasic acid chloride with a yield of 79.62%. The product obtained by the reaction did not require subsequent treatment and could be directly used in the next copolymerization modification experiment.

[0086] Preparation of modified para-aramid material based on this aromatic dibasic acid chloride:

[0087] 108g of p-phenylenediamine and 15g of anhydrous lithium chloride are dissolved in 600g of N-methylpyrrolidone solution after dehydration by molecular sieve, and the dissolved system is placed in an ice water bath at 0-4°C, 196.91g of terephthaloyl chloride and 8.66g of ferulic acid-derived diacyl chloride are weighed and mixed, and the sample is added to the polymerization solution four times, and the addition speed is controlled each time so that the temperature does not exceed 20°C. After the polymerization reaction is completed, the temperature is raised to 100°C, and 48.5g of calcium hydroxide is added to neutralize the hydrogen chloride generated by the reaction. After the reaction is completed, the polymerization stock solution is poured into methanol by solute phase separation method to precipitate pure resin, and the resin is dried to obtain the modified para-aramid resin.

[0088] Example 4

[0089] A method for preparing an aromatic dibasic acid chloride:

[0090] 20.71g of ferulic acid-derived dibasic acid was added to a 250mL round-bottom flask containing 150g of dichloroethane, and 28.4g of thionyl chloride and 100μL of catalyst DMF were added, and the reaction was refluxed at 75°C for 2h. After the reaction, the liquid raw material and the solvent were removed by reduced pressure distillation in a 50°C water bath to obtain 19.1g of ferulic acid-derived dibasic acid chloride with a yield of 80.46%. The product obtained by the reaction did not require subsequent treatment and could be directly used in the next copolymerization modification experiment.

[0091] Preparation of modified para-aramid material based on this aromatic dibasic acid chloride:

[0092] 108g of p-phenylenediamine and 15g of anhydrous lithium chloride are dissolved in 600g of N-methylpyrrolidone solution after dehydration by molecular sieve, and the dissolved system is placed in an ice water bath at 0-4°C, 195.9g of terephthaloyl chloride and 10.11g of ferulic acid-derived diacyl chloride are weighed and mixed, and the sample is added to the polymerization solution in four times, and the addition speed is controlled each time so that the temperature does not exceed 20°C. After the polymerization reaction is completed, the temperature is raised to 100°C, and 48.5g of calcium hydroxide is added to neutralize the hydrogen chloride generated by the reaction. After the reaction is completed, the polymerization stock solution is poured into methanol by solute phase separation method to precipitate pure resin, and the resin is dried to obtain the modified para-aramid resin.

[0093] Example 5

[0094] A method for preparing an aromatic dibasic acid chloride:

[0095] 20.71g of ferulic acid-derived dibasic acid was added to a 250mL round-bottom flask containing 150g of dichloroethane, and 26.2g of thionyl chloride and 100μL of catalyst DMF were added, and the reaction was refluxed at 80°C for 1h. After the reaction, the liquid raw material and the solvent were removed by vacuum distillation in a 50°C water bath to obtain 18.45g of ferulic acid-derived dibasic acid chloride with a yield of 77.72%. The product obtained by the reaction did not require subsequent treatment and could be directly used in the next copolymerization modification experiment.

[0096] Preparation of modified para-aramid material based on this aromatic dibasic acid chloride:

[0097] 108g of p-phenylenediamine and 15g of anhydrous lithium chloride are dissolved in 700g of N-methylpyrrolidone solution after dehydration by molecular sieve, and the dissolved system is placed in an ice water bath at 0-4°C, 192.85g of terephthaloyl chloride and 14.45g of ferulic acid-derived diacyl chloride are weighed and mixed, and the sample is added to the polymerization solution four times, and the addition speed is controlled each time so that the temperature does not exceed 20°C. After the polymerization reaction is completed, the temperature is raised to 100°C, and 48.5g of calcium hydroxide is added to neutralize the hydrogen chloride generated by the reaction. After the reaction is completed, the polymerization stock solution is poured into methanol by solute phase separation method to precipitate pure resin, and the resin is dried to obtain the modified para-aramid resin.

[0098] Example 6

[0099] A method for preparing an aromatic dibasic acid chloride:

[0100] 20.71g of ferulic acid-derived dibasic acid was added to a 250mL round-bottom flask containing 200g of dichloroethane, and 20g of thionyl chloride and 100μL of catalyst DMF were added, and the reaction was refluxed at 80°C for 1.5h. After the reaction, the liquid raw material and the solvent were removed by vacuum distillation in a 50°C water bath to obtain 18.5g of ferulic acid-derived dibasic acid chloride with a yield of 77.93%. The product obtained by the reaction did not require subsequent treatment and could be directly used in the next copolymerization modification experiment.

[0101] Preparation of modified para-aramid material based on this aromatic dibasic acid chloride:

[0102] 108g of p-phenylenediamine and 15g of anhydrous lithium chloride are dissolved in 600g of N-methylpyrrolidone solution after dehydration by molecular sieve, and the dissolved system is placed in an ice water bath at 0-4°C, 182.7g of terephthaloyl chloride and 28.3g of ferulic acid-derived diacyl chloride are weighed and mixed, and the sample is added to the polymerization solution four times, and the addition speed is controlled each time so that the temperature does not exceed 20°C. After the polymerization reaction is completed, the temperature is raised to 100°C, and 48.5g of calcium hydroxide is added to neutralize the hydrogen chloride generated by the reaction. After the reaction is completed, the polymerization stock solution is poured into methanol by solute phase separation method to precipitate pure resin, and the resin is dried to obtain the modified para-aramid resin.

[0103] Comparative Example 1

[0104] The comparative example is a foreign commercialized para-aramid fiber with the brand name Kevlar29, a tensile strength of 25.99 cn / dtex, and an elongation at break of 3.6%.

[0105] Comparative Example 2

[0106] The comparative example is a foreign commercialized para-aramid fiber, with the brand name Twaron HM1055, a tensile strength of 24.63 cn / dtex, and an elongation at break of 3.5%.

[0107] Comparative Example 3

[0108] This comparative example is a para-aramid copolymer modified material prepared by introducing an asymmetric diamine.

[0109] Specifically, 102.6g of p-phenylenediamine, 10g of asymmetric diamine monomer 3,4'-diaminodiphenyl ether, and 15g of anhydrous lithium chloride are dissolved in 600g of N-methylpyrrolidone solution after dehydration by molecular sieve, the dissolved system is placed in an ice water bath at 0-4°C, 213.15g of terephthaloyl chloride is weighed, and the acyl chloride monomer is added to the polymerization solution in four times, and the addition speed is controlled each time so that the temperature does not exceed 20°C. After the polymerization reaction is completed, the temperature is raised to 100°C, 48.5g of calcium hydroxide is added to neutralize the hydrogen chloride generated by the reaction, and after the reaction is completed, the polymerization stock solution is poured into methanol by solute phase separation method to precipitate pure resin, and the resin is dried to obtain the modified para-aramid resin.

[0110] Comparative Example 4

[0111] This comparative example is a para-aramid copolymer modified material prepared by introducing asymmetric meta-phenylenediamine.

[0112] Specifically, 102.6g of p-phenylenediamine, 5.4g of m-phenylenediamine, and 15g of anhydrous lithium chloride are dissolved in 600g of N-methylpyrrolidone solution after dehydration by molecular sieve, the dissolved system is placed in an ice water bath at 0-4°C, 213.15g of terephthaloyl chloride is weighed, and the acyl chloride monomer is added to the polymerization solution in four times, and the addition speed is controlled each time so that the temperature does not exceed 20°C. After the polymerization reaction is completed, the temperature is raised to 100°C, 48.5g of calcium hydroxide is added to neutralize the hydrogen chloride generated by the reaction, and after the reaction is completed, the polymerization stock solution is poured into methanol by solute phase separation method to precipitate pure resin, and the resin is dried to obtain the modified para-aramid resin.

[0113] The modified para-aramid resin obtained in the above example was dissolved in an organic solvent to test its solubility. The test conditions were heating and dissolving at 80°C for 3 hours, and the complete dissolution time was recorded. The modified para-aramid resin obtained in the example was further dissolved in a solvent for spinning, and the fiber mechanical properties were tested according to the standard of GB / T 19975-2005. The specific test results are shown in Table 1 below.

[0114] Table 1 Performance parameters of modified para-aramid

[0115]

[0116] From the data in Table 1 above, it can be seen that the elongation at break of the polymerized para-aramid material obtained in the embodiment gradually increases with the increase in the amount of asymmetric ferulic acid-derived dibasic acid chloride added, but the strength decreases, and the dissolution processing ability of the obtained modified para-aramid material is significantly improved. On the other hand, thanks to the presence of conjugated double bonds in the dibasic acid chloride structure synthesized and used in the present invention, compared with Comparative Example 3 in which other asymmetric monomers are used to improve the dissolution processing ability of para-aramid, the modified para-aramid materials obtained in the embodiments of the present invention have higher mechanical strength.

[0117] The method of destroying the original regular structure of para-aramid to improve the processing ability will inevitably cause a decrease in the strength of the material. The present invention provides a new modified monomer, ferulic acid-derived dibasic acid chloride, and further adjusts the proportion of added asymmetric monomers and other process parameters to significantly improve the processability of para-aramid materials while retaining the original mechanical strength as much as possible. The research results of the present invention show that the scheme of copolymerizing para-aramid with dibasic acid chloride derived from ferulic acid is feasible, and a para-aramid material with better comprehensive performance and easy processing can be obtained under the condition of maintaining a balance between breaking strength and elongation.

[0118] In addition, the inventors of this case also referred to the aforementioned embodiments and conducted experiments with other raw materials, process operations, and process conditions described in this specification, and obtained relatively ideal results.

[0119] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.

Claims

1. A ferulic acid-derived dibasic acid chloride compound, characterized in that: The structural formula of the ferulic acid-derived dibasic acid chloride compound is shown in formula (I):

2. A method for preparing a dibasic acid chloride compound derived from ferulic acid, characterized in that: include: reacting a ferulic acid-derived dibasic acid with thionyl chloride to obtain a ferulic acid-derived dibasic acid chloride compound; Wherein, the ferulic acid-derived dibasic acid has a structure shown in formula (II):

3. The preparation method according to claim 2, characterized in that: include: A mixed reaction system comprising a ferulic acid-derived dibasic acid, thionyl chloride, a solvent and a catalyst is heated and refluxed to obtain a ferulic acid-derived dibasic acid chloride compound.

4. The preparation method according to claim 3, characterized in that: The solvent includes any one of dichloromethane, dichloroethane, and chloroform, or a combination of two or more thereof; and / or, the mass ratio of the solvent to the ferulic acid-derived dibasic acid is 5 to 10:1; and / or, the molar ratio of thionyl chloride to the dibasic acid derived from ferulic acid is 1.5 to 3:1; and / or, the catalyst comprises N,N-dimethylformamide; And / or, the temperature of the heating reflux reaction is 50-80° C. and the time is 1-3 hours.

5. Use of the ferulic acid-derived dibasic acid chloride compound according to claim 1 in the preparation of copolymer-modified para-aramid resin.

6. A copolymer modified para-aramid resin, characterized in that: The structural formula of the copolymer modified para-aramid resin is shown in formula (III): Among them, m:n=90~99:10~1.

7. The method for preparing the copolymer-modified para-aramid resin according to claim 6, characterized in that: include: The ferulic acid-derived dibasic acid chloride compound, terephthaloyl chloride and p-phenylenediamine as claimed in claim 1 are mixed and polymerized to obtain the copolymer-modified p-aramid resin.

8. The preparation method according to claim 7, characterized in that: include: Under protective atmosphere conditions, p-phenylenediamine, a dissolving salt and a polymerization solvent are mixed to obtain a mixed solution; The mixed solution, the dibasic acid chloride compound derived from ferulic acid and terephthaloyl chloride are mixed to carry out the polymerization reaction to obtain the copolymer-modified para-aramid resin.

9. The preparation method according to claim 8, characterized in that: The protective atmosphere comprises a nitrogen atmosphere; And / or, the dissolution-advantage salt comprises lithium chloride or calcium chloride; And / or, the amount of the dissolution-aiding salt added is 2 to 10% of the mass of the polymerization solvent; and / or, the polymerization solvent comprises a polymerization solvent from which water is fully removed; and / or, the polymerization solvent comprises N-methylpyrrolidone or N,N-dimethylacetamide; And / or, the mass ratio of the polymerization solvent to p-phenylenediamine is 5 to 10:

1.

10. The preparation method according to claim 8, characterized in that: include: The ferulic acid-derived dibasic acid chloride compound and terephthaloyl chloride are mixed to obtain a mixed monomer, and the mixed solution is mixed with the mixed monomer to carry out the polymerization reaction.

11. The preparation method according to claim 10, characterized in that: The content of the ferulic acid-derived dibasic acid chloride compound in the mixed monomer is 1 to 10 mol%; and / or, the molar ratio of the mixed monomer to p-phenylenediamine is 1.05 to 1.2:1; And / or, the preparation method comprises: adding the mixed monomer into the mixed solution in multiple times.

12. A copolymer-modified para-aramid fiber obtained by processing the copolymer-modified para-aramid resin according to claim 6.

13. A solution processing method, characterized in that: The method comprises dissolving the copolymer-modified para-aramid resin as claimed in claim 6 in a solvent.

14. The solution processing method according to claim 13, characterized in that: The solvent includes any one of N-methylpyrrolidone, N,N-dimethylacetamide and concentrated sulfuric acid or a combination of two or more thereof.

Citation Information

Patent Citations

  • Para-aramid dissolving system and application thereof, aramid diaphragm and preparation method thereof, and aramid ceramic composite diaphragm and preparation method thereof

    CN115663394A

  • Preparation method of para-meta copolymerized aramid fiber

    CN118007259A

Cited By

  • Polyamide PPS composite material and preparation method thereof

    CN120329729A

  • Battery diaphragm containing pyridyl heterocyclic aramid as well as preparation method and application of battery diaphragm

    CN120565996A

  • A battery separator containing pyridine-based heterocyclic aramid fibers, its preparation method and application

    CN120565996B